COULD SATISFACTION ON THE AIRLINE’S SERVICE QUALITY (AIRQUAL) MAKE LION AIR’S CUSTOMERS TRUST AND BECOME LOYAL TO THE AIRLINE COMPANY? - Devi Angrahini Anni Lembana; Reina Valucy (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2018)
The Indonesian public interest in using the service flights as their means of transportation is remarkably growing according to Indonesia Investment data in 2017. People tend to use service flights because of Indonesia’s unique geographical nature and airline tickets becomes increasingly affordable as the growth low-cost carrier. The purpose of this research is to investigate the role of customer satisfaction toward the airline’s service quality (AIRQUAL) in effecting trust and loyalty. The study was directly conducted by collecting primary data by randomly distribute 252 questioners to respondents that were boarding gate terminal 1A and 1B at the Soekarno Hatta International Airport. Hypotheses were then statistically tested using structural equation model. The results of this research show that satisfaction can make customer whose satisfied with the quality of the airline service become loyal to Lion Air. On the contrary, satisfaction cannot make the customer trust Lion Air as an airline company, even though they already satisfied with the quality of airline service.